2012
DOI: 10.1177/1090198111436340
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Access and Health Behaviors Among Men Who Have Sex With Men

Abstract: Men who have sex with men (MSM) appear to experience barriers to health care compared with general population men. This report examines individual differences in health care access within a diverse sample of urban MSM (N = 871). The authors examined demographic differences in health care access and the relation between access and health-related attitudes, health behaviors, and HIV transmission risk. They operationalized health care access in terms of three indicators: perceived barriers, insurance status, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 35 publications
0
57
1
1
Order By: Relevance
“…30,31 Previous studies have shown that healthy MSM access healthcare less than the general male population. 32,33 Our study suggests that accessing PrEP may be a gateway for MSM to engage in regular HIV/STI testing, health monitoring, and other preventive services. The client-centered care that participants received also encouraged honest reporting of missed pills at the SF site.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Previous studies have shown that healthy MSM access healthcare less than the general male population. 32,33 Our study suggests that accessing PrEP may be a gateway for MSM to engage in regular HIV/STI testing, health monitoring, and other preventive services. The client-centered care that participants received also encouraged honest reporting of missed pills at the SF site.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that mistrust, disclosure difficulties, and internalized homophobia may limit healthcare access and delay presentation for care among MSM. [11][12][13][14] A recent study of New York MSM found that although most had seen a clinical provider recently, 39 % did not disclose sexual activity with male partners, with lower rates among African American and Latino MSM. 15 Medical mistrust, [16][17][18][19] discrimination experiences, [18][19][20][21] conspiracy beliefs, 19,22,23 and concerns about disclosure may be particularly significant barriers to PrEP access among MSM of color, as demonstrated by a recent PrEP acceptability study among African American MSM.…”
mentioning
confidence: 99%
“…Mistrust is associated with avoidance of HIV testing and poor treatment adherence (Hill & McNeely, 2013;Millett et al, 2012). McKrinan et al (2012) suggested that ''men who experience stigma or barriers within health care settings may avoid personal disclosure, whereas men who are loathe to disclose their sexual orientation may avoid health care settings' ' (p. 38).…”
Section: How Is Homophobia Linked To Hiv Transmission?mentioning
confidence: 98%
“…Homophobic sentiment is embedded in laws and social policies in the United States, subsequently undermining the health of MSM. MSM lack same-sex marriage rights or domestic partner benefits in many states, which limits their access to health care and insurance (McKrinan, Du Bois, Alvy, & Jones, 2012). In states where same-sex marriage is not legal, there are insurmountable financial barriers to preexposure prophylaxis and antiretroviral therapy (ART) if one partner has HIV (Human Rights Campaign, 2014).…”
Section: How Is Homophobia Linked To Hiv Transmission?mentioning
confidence: 99%